New enzyme immunoassay for detecting total, type I, and type II intrinsic factor antibodies. Issue 3 (March 1989) - Waters, H M; Smith, C; Howarth, J E; Dawson, D W; Delamore, I W
Abstract : A method for the detection of total, type I, and type II intrinsic factor antibodies was devised. The technique comprises a two-site solid phase enzyme linked immunosorbent assay (ELISA), with human intrinsic factor conjugated with horseradish peroxidase as label and attached to polystyrene tubes as solid phase. One conjugation provides sufficient material to assay more than 10, 000 patient samples. The label proved stable during the course of this evaluation and was still in use more than 12 months after preparation. When applied to 45 serum samples from cases of pernicious anaemia, intrinsic factor antibodies were shown in 30 (67%). Simplicity, high capacity, low cost and label stability, combined with relatively high clinical sensitivity make the method suitable for cost effective screening of large numbers of samples. Simple modifications to the basic assay reagents permitted type I and type II intrinsic factor antibodies to be differentiated.